A Qualitative Historical Review of Educational Paradigm Shifts in Pre-Modern Sri Lanka (Prehistoric Settlements to c. 1505 CE) - Kolabagama Nugawelage Thushari Upuli Samaraweera; Lanka Nanayakkara Pathiranage Wedikandage (Eduscape : Journal of Education Insight, 2026)
The current literature on pre-modern Sri Lanka has discussed monastic establishments, preservation of the Pali literature, and the colonial educational reforms, in few cases in isolation. Remains to be answered is a systematic, long-term rebuilding of how the mechanisms of knowledge transmission changed over different historical periods between prehistoric oral to script-based monasticism to the institutionalization of the Pirivena system within one analytical paradigm. The paper will attempt to fill in such a historiographical gap by characterizing it using qualitative historical analysis of primary textual documents, namely, the Mahavamsa and Dipavamsa chronicles with supplementation by evidence of early Brahmi epigraphic sources, archaeological evidence in prehistoric and monastic settings, and critically analyzed secondary historiography. Thematic and chronological analysis was employed in a combination with cross-source triangulation to determine three consecutive but overlapping periods of education between about 125,000 BCE and c. 1505 CE. In the study the pre-modern education in Sri Lanka could not be reduced to religious education but instead was the inclusion of grammar, logic, medicine, and administrative knowledge. The article provides a historiographical based reconstruction of the long-term pedagogical transformation, criticizes reductionist explanations of pre-modern learning in Sri Lanka and identifies the island as part of wider scholarly South Asian intellectual communities.